DETERMINATION OF THERMOREOLOGICAL CHARACTERISTICS AT MICROSCOPIC SCALE FROM EXPERIENCES ON THIN WALL TUBES - Marina, Vasile; Marina, Viorica (Journal of Engineering Science (Chişinău), 2018)
The relationships between the module of stress and strain tensor deviator, in the case of thermorheological processes, are modeled by using the structural model. It is shown that sub-element properties can be determined from some experiences on thin walls tubes loaded with axial forces and interior pressure. Because the constants and material functions for this material are unknown the loaded conditions with constant state parameters are required. If the stretching process is produced with a constant speed of axial strain for each material there is one constant report among axial and circumstantial stresses which ensures in isothermal processes state constant parameters